The Qur’anic hapax legomenon "sִamad" in Medieval Arab-Christian apologetics - Vladislava Shtefan (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
The situation that emerged in the period of VIII-X centuries, when representatives of the Abbasid dynasty (750-1258), who had recently come to power, began to actively encourage the conversion of non-believers to Islam, prompted representatives of different ethno-confessional groups (Melkites, Jacobites, Nestorians) to react immediately: apologetic and polemical literature was created; moreover, many treatises often concealed the experience of the author's real participation in the discussions. This paper analyses the use of Sura 112 in Arab-Christian apologetic literature. Sura 112, despite its brevity (consisting of four ayats), occupies a special place in the Qur'anic corpus because it expresses in a concentrated form the key dogma of Islam about monotheism (tawhid). The Surah is also distinguished by the presence of a word not found in the Qur'an (the so-called hapax legomenon), ṣamad, which has given rise to a wide range of interpretations both in the Muslim tradition and in Byzantine polemical literature. For Arab-Christian authors who lived in the same territory as Muslims, the dialogue with Islam was even more relevant, but not in a polemical, as in Byzantium, but in an apologetic way, and Sura 112 was also the object of their attention.